Challenges in the Daily Living Activities of Patients with Multiple Sclerosis: A Qualitative Content Analysis - Ali Dehghani; Mahsa Khoramkish; Sara Shahsavari Isfahani (Shiraz University of Medical Sciences, 2019)
Background: Multiple sclerosis (MS) is a chronic nervous system disease with a wide range of symptoms that affect the self-care ability of patients in daily activities of life; the patients afflicted with this disease face with many challenges. This study was conducted to explore the activities of daily living (ADL) challenges of these patients. Methods: In this conventional content analysis study, fourteen MS patients who were selected purposively from Iran MS Society in Jahrom (Iran) participated in 2018. Data were gathered using semi-structured and in-depth interviews. A total of 14 interviews were conducted. These data were analyzed using MAXQDA 10 Software and the Graneheim and Lundman method. Results: Analysis of data led to extraction of the main theme "fear of ambiguous future of diseases" as the most important daily living challenge in MS patients. This challenges were categorized in four main categories: 1) confrontation to physical, emotional, psychological and behavioral changes, 2) fear of becoming crippled, 3) tolerance of financial burden of the disease, and 4) confrontation to culturalsocial wrong beliefs. Conclusion: The results of this study showed that people with MS face a number of ADL challenges. Fear of an ambiguous future leads to problems in ADL of patients. Therefore, considering the ADL challenges, health care personnel especially nurses, family members and social organizations can improve ADL and compromise patients with the disease as much as possible by providing conditions for application of the self-care activities and their implementation by patients.